Understanding the Underlying Knowledge Structure in Business Ethics, Governance and Sustainability Research - Duara, Mridusmita; Khandelwal, Vinay; Kumar, C.T. Sunil; Chotia, Varun; Sharma, Prashant (International Review of Management and Marketing, 2024)
Given their significant role, this study aims to comprehensively understand the linkages between business ethics, governance, and Sustainability research. The study is focused on knowing the knowledge structure that connects these concepts, identifying the critical areas of focus, and tracking their evolution over time. A comprehensive analysis was conducted on a data set covering 2003 to 2024. Two worldwide repute databases, namely, Scopus and Web of Science (WoS), were used to search scientific publications (Sharma et al. 2023; Sharma et al. 2024). The selection process adhered to the inclusion and exclusion criteria outlined in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. The Structural Topic Modeling (STM) approach was employed to group related data segments, revealing underlying patterns and significant content. Specific latent topics such as Experiential learning, corporate governance structure and behavior, Sustainability through energy policy, and Environmental protection acts were identified, which depicted the underlying knowledge areas in this field of study. Future research in business ethics and corporate Sustainability must pay attention to the emerging contextual issues in business contexts and make the future study of business ethics and corporate sustainability move beyond traditional totems and taboos in social ventures, family businesses, start-ups, and SMEs.